Peningkatan Literasi Finansial dan Pengelolaan Keuangan Rumahtangga Nelayan Pesisir Banten Lama - Mirajiani, Mirajiani (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2025)
The role of women, particularly housewives, is crucial in fishermen households due to the cultural norm in which financial management is predominantly handled by them. However, one of the pressing issues currently faced by these communities is the low level of financial literacy among fishing households. This paper aims to explore efforts to improve financial literacy and household financial management among fishermen families in the coastal area of Banten Lama. The method employed to achieve this goal is a Participatory Action Research (PAR) approach, which actively involves fisherwomen in every stage of the financial management process. The role of women, especially housewives in this region, is vital because they are directly involved in post-harvest fishery activities, particularly in processing fish catches, and are responsible for managing household finances. The key aspects of financial literacy and household financial management that need to be implemented in this area include: (1) Enhancing financial literacy and education, (2) Strengthening entrepreneurial skills, and (3) Improving access to financial services and empowering fisherwomen's financial groups.